Hot Coffee: The Identity, Climate Profiles, Agronomy, and Beverage Characteristics of Coffea racemosa and C. zanguebariae - Davis, Aaron P.; Gargiulo, Roberta; Almeida, Iolanda N. das M.; Caravela, Marcelino Inácio; Denison, Charles; Moat, Justin (Frontiers in Sustainable Food Systems, 2021)
Climate change poses a considerable challenge for coffee farming, due to increasing temperatures, worsening weather perturbations, and shifts in the quantity and timing of precipitation. Of the actions required for ensuring climate resilience for coffee, changing the crop itself is paramount, and this may have to include alternatives using alternative coffee crop species. In this study we use a multidisciplinary approach to elucidate the identity, distribution, and attributes, of two minor coffee crop species from East Africa: Coffea racemosa and C. zangubariae. Using DNA sequencing and morphology, we elucidate their phylogenetic relationships and confirm that they represent two distinct but closely related species. Climate profiling is used to understand their basic climatic requirements and compared these to those of Arabica (C. arabica) and robusta (C. canephora) coffee. Heat tolerance, low mean annual precipitation and pronounced precipitation seasonality, are identified and discussed. Basic agronomic data (including yield) and sensory data are also provided and evaluated. Coffea racemosa and C. zangubariae species possess useful traits for coffee crop plant development, particularly heat tolerance, low precipitation requirement, high precipitation seasonality, and fruit development duration. These attributes would be best accessed via breeding programs, although these species have niche-market potential via pre-farm selection.